When media allow the user to interact, play and share: recent perspectives on interactive documentary. Issue 4 (2nd October 2019) - Vázquez-Herrero, Jorge; López-García, Xosé
ABSTRACT: The evolution of digital media has inspired new narrative forms within the media context. In the last few years, interactive documentary has presented complex and alternative ways to access information. This article presents an analysis of this statement consisting of the case study of five international productions: Bear 71, A Short History of the Highrise, Pirate Fishing, Do Not Track and Párkinson, que tiemble el camino . The production of interactive documentary in online media as a journalistic format is tackled with a multidimensional approach which incorporates the product, the user's perception and the author's view. The exploration of new formats in online media is linked to innovation and a contemporary response to the audiences, who are now able to interact, play and share in an environment favoured by mobile communication and the skills of the current society.